Article Review: Immunomudulatory Activity of Pegagan Embun (Hydrocotyle sibthorpioides Lam.) Extract - Adrul Fauzan; Yufri Aldi; Salman Umar; Afriwardi Afriwardi (JURNAL PROTEKSI KESEHATAN, 2023)
Various kinds of diseases can be caused by exposure to objects that are not recognized by the body. To recognize these foreign objects, a good immune system is needed. Immunomodulators are substances used to exert an effect on the immune system. The function of an immunodulator in the body can be as an immunostimulant, namely by stimulating the function of the immune system. Immunostimulating compounds can be obtained from plants. One of the plants that can be used is pegagan embun (Hydrocotyle sibthorpioides Lam.). In Hydrocotyle sibthorpioides Lam. It contains flavonoid compounds which have immunomodulatory activity. This article review was conducted to obtain information related to the immunomodulatory potential of the Hydrocotyle sibthorpioides Lam plant. The writing method for making this research article review was a comparative method, namely taken from a collection of national journals and international journals. Various research results that have been obtained prove that the extract of Hydrocotyle sibthorpioides Lam. can potentially enhance the body's immune system due to the content of flavonoid compounds which function as natural immunomodulators.